Instantaneous threat escape and differentiated refuge demand among zooplankton taxa. Issue 2 (7th March 2016) - Hansson, Lars‐Anders; Bianco, Giuseppe; Ekvall, Mikael; Heuschele, Jan; Hylander, Samuel; Yang, Xi
Abstract: Most animals, including aquatic crustacean zooplankton, perform strong avoidance movements when exposed to a threat, such as ultraviolet radiation (UVR). We here show that the genera Daphnia and Bosmina instantly adjust their vertical position in the water in accordance with the present UVR threat, i.e., seek refuge in deeper waters, whereas other taxa show less response to the threat. Moreover, Daphnia repeatedly respond to UVR pulses, suggesting that they spend more energy on movement than more stationary taxa, for example, during days with fluctuating cloud cover, illustrating nonlethal effects in avoiding UVR threat. Accordingly, we also show that the taxa with the most contrasting behavioral responses differ considerably in photoprotection, suggesting different morphological and behavioral strategies in handling the UVR threat. In a broader context, our studies on individual and taxa specific responses to UVR provide insights into observed spatial and temporal distribution in natural ecosystems.